Cell-penetrating peptides as transporters for morpholino oligomers: effects of amino acid composition on intracellular delivery and cytotoxicity - Wu, Rebecca P. (Oxford University Press, 2007)
Arginine-rich cell-penetrating peptides (CPPs) are promising transporters for intracellular delivery of antisense morpholino oligomers (PMO). Here, we determined the effect of L-arginine, D-arginine and non-α amino acids on cellular uptake, splice-correction activity, cellular toxicity and serum binding for 24 CPP−PMOs. Insertion of 6-aminohexanoic acid (X) or β-alanine (B) residues into oligoarginine R(8) decreased the cellular uptake but increased the splice-correction activity of the resulting compound, with a greater increase for the sequences containing more X residues. Cellular toxicity was not observed for any of the conjugates up to 10 μM. Up to 60 μM, only the conjugates with ⩾ 5 Xs exhibited time- and concentration-dependent toxicity. Substitution of L-arginine with D-arginine did not increase uptake or splice-correction activity. High concentration of serum significantly decreased the uptake and splice-correction activity of oligoarginine conjugates, but had much less effect on the conjugates containing X or B. In summary, incorporation of X/B into oligoarginine enhanced the antisense activity and serum-binding profile of CPP−PMO. Toxicity of X/B-containing conjugates was affected by the number of Xs, treatment time and concentration. More active, stable and less toxic CPPs can be designed by optimizing the position and number of R, D-R, X and B residues.